2021
DOI: 10.1177/09596836211011678
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the retreat of the Aneto Glacier (Spanish Pyrenees) since the Little Ice Age, and its accelerated shrinkage over recent decades

Abstract: The Aneto, located on the Maladeta Massif (Central Pyrenees), is the largest glacier of the Pyrenees. The glacier is 675 m long, occupies an area of 48.64 ha and has a maximum altitude of 3269 m. In this study, we present a detailed area, volume, ice thickness, and Equilibrium Line Altitude reconstruction of the glacier for different periods (LIA, 1957, 1983, 2000, 2006, 2015, and 2017) and analyze its retreat. To estimate the glacier extent during the LIA, the moraines were mapped by using photo interpretatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 76 publications
0
3
0
Order By: Relevance
“…For example, between the LIA and 2012, the total area of the small glaciers in the Julian Alps decreased from 2.367 to 0.383 km 2 , and the largest of them, Canin glacier, shrank by 88% [54]. Triglav glacier in the Julian Alps of Slovenia diminished even more: from 22 ha in 1897 to between 0.7 and2 ha in 2000-2014 [41,55], the Calderone glacier in the Apennines-from 9.88 ha in 1884 to 3.5 ha in 2006 [45,56], Debeli Namet glacier in the Durmitor-from 11 ha in 1878 to an average of 2.1 ha for 2011-2021 [14,15,46], Aneto glacier in the Pyrenees-from 245 ha in 1850 to 48 ha in 2017 [57,58]; and Monte Perdido glacier in the Pyrenees (from 556 ha in 1850 to 38 ha in 2016) [50,53]).…”
Section: Discussionmentioning
confidence: 99%
“…For example, between the LIA and 2012, the total area of the small glaciers in the Julian Alps decreased from 2.367 to 0.383 km 2 , and the largest of them, Canin glacier, shrank by 88% [54]. Triglav glacier in the Julian Alps of Slovenia diminished even more: from 22 ha in 1897 to between 0.7 and2 ha in 2000-2014 [41,55], the Calderone glacier in the Apennines-from 9.88 ha in 1884 to 3.5 ha in 2006 [45,56], Debeli Namet glacier in the Durmitor-from 11 ha in 1878 to an average of 2.1 ha for 2011-2021 [14,15,46], Aneto glacier in the Pyrenees-from 245 ha in 1850 to 48 ha in 2017 [57,58]; and Monte Perdido glacier in the Pyrenees (from 556 ha in 1850 to 38 ha in 2016) [50,53]).…”
Section: Discussionmentioning
confidence: 99%
“…According to our results, during this phase, the main Upper Garonne Glacier was ~ 78 km long and covered ~ 900 km 2 . Considering the position of the frontal moraine ridge EM-2 at 480 m, and the derived palaeoglacier reconstruction, the ELA was located at 1711 ± −65/55 m (AAR), 1719 ± −95/60 m (global AABR) and 1704 ± −105/70 m (mid-latitude AABR), with an average of 1711 m. This altitude suggests a reduction of 9.3 °C with respect of current ELA at 3139 m and assuming no change in the summer precipitation (Campos et al 2021). As expected, these results show that glaciers had similar extents in the terminal basin during the MIS 6 and lLGM glacial advances and thus climate conditions were probably similar (Fernandes et al 2017).…”
Section: Chronology Of the Glacial Advances In The Upper Garonne Valleymentioning
confidence: 82%
“…[Paul and Bolch, 2019] reviewed a number of studies of the evolution of Alpine glaciers since the LIA and concluded that it could be summarized by a km scale retreat, a rise in the equilibriumline altitude (ELA) of 100-200 m, and an up-valley retreat of several hundred meters in glacier terminus positions. In Pyrenean glaciers, Campos et al [2021] reported ELA rises of 220 m.…”
Section: Introductionmentioning
confidence: 99%